Knowledge and perception on continuous ambulatory peritoneal dialysis among physicians working in selected public hospitals in Myanmar - Pyar, Khin Phyu; Myint, Moe Zaw; Kyaw, Aung Phyoe; Lwin, Kyaw Thu Yein; Maung, Lay Maung; Hein, Ye Min; Hla, Sai Aik; Win, Thurein; Aung, Zarni Htet; Myint, Thein Tun; Aung, Han Lin; Maung, Kyaw Thet; et al. (Jour Med Resh and Health Sci, 2023)
Background: Peritoneal dialysis (PD) is a form of renal replacement therapy and is used for acute kidney injury as well as end stage renal disease (ESRD). For patients with ESRD, either CAPD (continuous ambulatory peritoneal dialysis) or hemodialysis (HD) is used to replace the function of kidneys; at present, in center HD is the main treatment option in Myanmar. CAPD is generally advisable in developing countries particularly in remote areas as in-center HD is not accessible in all areas. This study aimed to assess the knowledge and perception on continuous ambulatory peritoneal dialysis among physicians working at public hospitals in Myanmar. Methods: A cross-sectional descriptive study was conducted among physicians, working at public hospitals in Myanmar; done in February 2023. Data were collected by using standardized forms and analysis was done. Results: Among 104 physicians, the youngest was 26 years and the oldest was 88 years. More than half (57%) were working in hospitals with HD center. Less than 10% of physicians were caring cases with CAPD; less than 7% of physicians had experience with peritoneal dialysis (PD) for acute kidney injury. Regarding treatment of acute kidney injury, most of physicians (60.6%) thought that HD was better than PD; however, less than half (41.3%) of them thought that the efficacy of CAPD was the same as HD in caring patients with ESRD. Their knowledge on CAPD was good. Their agreement percentage on the advantages of CAPD over HD was as follows: patients with difficult vascular access (88%); hypotension (65% ); heart failure (44%); and arrhythmia (42%). Their view on likely obstacles to CAPD (in percentage) were supply of PD solutions (71%); skin infection over abdominal wall (68%); morbid obesity (53.8%);and, PD catheter related problems (42%). From their view, the likely reasons for not establishing CAPD in Myanmar (in percentage) were suboptimal health education among general population (64%), difficulty in supply of PD fluids (64%) and technical problems (52%). Three quarter thought that CAPD was safer than HD in COVID era. Nearly ninety percent (85.6%) were willing to get the training course on CAPD. Sixty percent of them preferred CAPD as home-based dialysis therapy (BDT) if they had a chance to make shared decision with the patients to choose between in center HD and HBDT; and they expected that the cost of CAPD should be cheaper than HD. Most of them obtained information on CAPD from internet; less than half (45%, 47/104) received training from workshop. Conclusions: Their knowledge on PD was good though less than half attended workshop on CAPD. The experience on CAPD was very limited. Their perception on CAPD was positive and they want to recommend home dialysis in form of CAPD.